Ethylene: Management and breeding for postharvest quality in vegetable crops. A review - Cocetta, Giacomo; Natalini, Alessandro (Frontiers in Plant Science, 2022)
Ethylene is a two-carbon gaseous plant growth regulator that involved in several important physiological events, including growth, development, ripening and senescence of fruits, vegetables, and ornamental crops. The hormone accelerates ripening of ethylene sensitive fruits, leafy greens and vegetables at micromolar concentrations, and its accumulation can led to fruit decay and waste during the postharvest stage. Several strategies of crops management and techniques of plant breeding have been attempted in the last decades to understand ethylene regulation pathways and ethylene-dependent biochemical and physiological processes, with the final aim to extend the produce shelf-life and improve the postharvest quality of fruits and vegetables. These investigation approaches involve the use of conventional and new breeding techniques, including precise genome-editing. This review paper aims to provide a relevant overview on the state of the art related to the use of modern breeding techniques focused on ethylene and ethylene-related metabolism, as well as on the possible postharvest technological applications for the postharvest management of ethylene-sensitive crops. An updated view and perspective on the implications of new breeding and management strategies to maintain the quality and the marketability of different crops during postharvest are given, with particular focus on: postharvest physiology (ethylene dependent) for mature and immature fruits and vegetables; postharvest quality management of vegetables: fresh and fresh cut products, focusing on the most important ethylene-dependent biochemical pathways; evolution of breeding technologies for facing old and new challenges in postharvest quality of vegetable crops: from conventional breeding and marker assisted selection to new breeding technologies focusing on transgenesis and gene editing. Examples of applied breeding techniques for model plants (tomato, zucchini and brocccoli) are given to elucidate ethylene metabolism, as well as beneficial and detrimental ethylene effects.